(untitled) (Eurasian Journal of Engineering and Technology, 2026)
This thesis presents the modeling and control of an induction motor drive using the Indirect Field-Oriented Control (IFOC) strategy. The proposed system employs a decoupled control structure, allowing independent regulation of torque and flux components through dq-axis transformation. A closed-loop control scheme is developed, consisting of an outer speed loop and inner current control loops, implemented using PI controllers. The reference voltages are generated in the synchronous reference frame and applied to the motor through a PWM-based voltage source inverter. The proposed approach ensures fast dynamic response, precise speed regulation, and reliable operation, making it well suited for application in AC electric locomotive traction systems.